Benign leiomyoma metastasizing to multiple organs and literature review - Gagliardi c, Polonsky A, wright A, (Journal of Medical Biomedical and Applied Sciences, 2016)
Uterine leiomyomas are highly common. Their incidence is generally cited as 20-25%, but has been Â shown to be as high as 70-80% in studies using histologic or sonographic examination. Distant metastasis is extremely rare and is of unknown etiology. It primarily affects women of reproductive age and Â might appear years after gynecological procedures such as myomectomy or hysterectomy.